Scrutinizing Self-Assembly, Surface Activity and Aggregation Behavior of Mixtures of Imidazolium Based Ionic Liquids and Surfactants: A Comprehensive Review - Kumar, Harsh; Kaur, Gagandeep (Frontiers in Chemistry, 2021)
The desire of improving various processes like enhanced oil recovery (EOR), water treatment technologies, biomass extraction, organic synthesis, carbon capture etc. in which conventional surfactants have been traditionally utilized; prompted various researchers to explore the self-assembly and aggregation behavior of different kinds of surface-active molecules. Ionic liquids (ILs) with long alkyl chain present in their structure constitute the advantageous properties of surfactant and ILs, hence termed as surface-active ionic liquids (SAILs). The addition of ILs and SAILs significantly influence the surface-activity and aggregation behavior of industrially useful conventional surfactants. After a brief review of ILs, SAILs and surfactants, the prime focus is made on analyzing the self-assembly of SAILs and the mixed micellization behavior of conventional surfactants with different ILs.